ANALISIS DAMPAK LALU LINTAS AKIBAT PEMBANGUNAN BEST WESTERN STAR HOTEL DAN STAR APARTEMENT SEMARANG TERHADAP KINERJA JARINGAN JALAN SEKITAR - Hayu Rahayu; Misi H. Wijaya; Bagus Hario Setiadji; Wahyudi Kushardjoko (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Best Western Star Hotel and Star apartments located in the MT. Haryono are currently being built into the new residential alternative in Semarang. This triggers resurgence, resulting jam in the area will increasing. The situation of the MT. Haryono street before Best Western Star Hotel and Star Apartments are built was very crowded in the morning, afternoon and evening due to the shopping and offices centers. Because of these problems, it will be planned traffic management, road widening, and green design time. In this study will be discuss about traffic performance’s existing, traffic performance after the construction of the building, traffic performance in 2018, and traffic performance after the application of some solutions. The analysis method that will be used is the analysis method of MKJI 1997. The method is used to analyze the condition of roads and hotspot intersections. Vast amount of hotel rooms and apartment per unit is calculated to obtain the resurgence happened. The amount of Best Western Star Hotel and Star Apartment’s resurgence then charged on each road, after getting overburdened volume of traffic resurgence, do the analysis of road and hotspot intersections performances. From the amount list of vehicles in each years from 2007 through 2011 was found the growth rate. The growth rate is used to predict the traffic conditions for the coming 5 years, so it can be selected the solution that can solve the problems for the coming 5 years. Test result are as follows : 1). The Best Western Star Hotel and Star Apartment’s resurgence caused 844 pcu/hour. 2). The growth rate of the vehicle is 3,94% per year. 3). The traffic management deemed not able to overcome the jam’s problems that occured. 4). Need to do road widening at Sriwijaya street and transforming the Lampersari street to become 1-way street. 5). Need to do redesign the green time.